Association Between Falls Experience and Physical Performance Measures in Community-Living Older Adults. (2nd April 2020) - Ganesh, G. Shankar; Dakshinamoorthy, Anandhi; Ponmathi, P.; Swain, Subhashisa
Abstract: Aims: To determine if various physical performance tests are able to adequately discriminate older adults based on their experience with falls and assess the concurrent validity of the "Barthel index" against these tests. Methods: Fifty-four older adults above 60 years of age were divided into three groups: those who suffered a fall, have fear of fall (FoF), or were part of an age-matched control group. Performance measures that quantified balance impairments, the strength of the trunk, and respiratory muscles along with the Barthel index were evaluated. Results: Older people who have experienced falls have lower scores in all the variables measured compared to the other two groups. Though certain measures were able to discriminate the scores between the three groups, not all of these measures were related to Barthel index scores. Conclusion: The Berg Balance Scale (BBS) seems to be more appropriate for discriminating balance impairment and performance among elders.